Efek Limpahan dari Smart Tourism: Analisis Interregional Input Output (IRIO) - Fitri Handayani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
The pandemic crisis in 2020 has significantly impacted the tourism sector. Besides, the tourism sector is a sector that has great potential in the economy and is an alternative to replacing the extractive sector, such as coal mining. Furthermore, new concepts related to smart tourism are also starting to emerge, which is expected to help accelerate economic recovery. Based on this, this study aims to evaluate the economic effects of smart tourism, both intra- and inter-regional effects, using inter-regional input-output. This is the first study to discuss the regional linkages to smart tourism. The result shows that smart tourism in Indonesia has a spillover effect to other regions, which can help regional integration. The smart tourism industry has a larger total effect on value-added than other industries. In intraregional, the multiplier effect on output, income, and value-added is greater than other industries. The biggest spillover effect of smart tourism is Java and Nusa Tenggara. Based on forward and backward linkage analysis, smart tourism in Bali is classified as "dependent on inter-industrial demand as an intermediate primary production." In addition, smart tourism can be categorized as a key sector in intra regional Bali. With the investment simulation in the smart tourism industry, it can be forecasted that Indonesia's economic growth in 2022 will increase by 0.035 percent; Bali by 2.2 percent; and other provinces by 0.006 percent, given the improvement of other industries.